N/S Co-doped Carbon Derived From Cotton as High Performance Anode Materials for Lithium Ion Batteries - Xiong, Jiawen; Pan, Qichang; Zheng, Fenghua; Xiong, Xunhui; Yang, Chenghao; Hu, Dongli; Huang, Chunlai (Frontiers in Chemistry, 2018)
Highly porous carbon with large surface areas is prepared using cotton as carbon sources which derived from discard cotton balls. Subsequently, the sulfur-nitrogen co-doped carbon was obtained by heat treatment the carbon in presence of thiourea and evaluated as Lithium-ion batteries anode. Benefiting from the S, N co-doping, the obtained S, N co-doped carbon exhibits excellent electrochemical performance. As a result, the as-prepared S, N co-doped carbon can deliver a high reversible capacity of 1101.1 mA h g-1 after 150 cycles at 0.2 A g-1, and a high capacity of 531.2 mA h g-1 can be observed even after 5000 cycles at 10.0 A g-1. Moreover, excellently rate capability also can be observed, a high capacity of 689 mA h g-1 can be obtained at 5.0 A g-1. This superior lithium storage performance of S, N co-doped carbon make it as a promising low-cost and sustainable anode for high performance lithium ion batteries.